Atherosclerosis in Systemic Lupus Erythematosus - Stojan, George (J Cardiovasc Pharmacol, 2013)
Accelerated atherosclerosis and its long-term sequelae are a major cause of late mortality among patients with systemic lupus erythematosus (SLE). Traditional Framingham risk factors such as hypertension, hypercholesterolemia, diabetes, and smoking do not account in entirety for this risk. SLE specific factors like disease activity and duration, use of corticosteroids, presence of antiphospholipid antibodies, and others are important risk factors. SLE is considered a coronary heart disease; equivalent and aggressive management of all traditional risk factors is recommended. Despite their role in primary and secondary prevention in the general population, statins seem to have no effect on cardiovascular outcomes in adult or pediatric SLE populations. The use of hydroxychloroquine has a cardioprotective effect, and mycophenolate mofetil may reduce cardiovascular events based on basic science data and data from the transplant population. The role of vitamin D supplementation and treatment of hyperhomocysteinemia remain controversial, but due to the safety of therapy and the potential benefit, they remain as optional therapies.